Channelization and flow depletion shift benthic macroinvertebrate and fish communities in urban rivers - Shufeng Chen; Changcheng Guo; Xu Wang; Yalin Wu; Yidong Wang; Yinhua Wang; Hongyu Guo (PLoS ONE, 2025)
Aquatic ecosystems worldwide are increasingly affected by human activities, with urbanization representing a major source of environmental stress. Channelization and flow depletion are key stressors in urban aquatic ecosystems. However, the combined effects of these factors on benthic macroinvertebrate and fish communities in urban rivers remain poorly understood. We examined the ecological impacts of channelization and flow depletion on benthic macroinvertebrates and fish in four urban rivers in Beijing, China: the natural high-flow Yongding River, the natural low-flow Gaojinggou River, the artificial high-flow Yongding River Diversion Channel, and the artificial low-flow Renmin Channel. By analyzing community composition, diversity, biomass, and water quality parameters, we assessed how river type (natural vs. artificial) and flow conditions (high vs. low) shape macroinvertebrate and fish communities across these urban rivers. Results showed that artificial channels had higher water temperatures, lower pH and DO, and higher concentrations of COD, NH4+, TP, fluorides, and sulfides compared to natural rivers, with flow depletion intensifying these effects. Both macroinvertebrate and fish community compositions varied significantly between river types and flow conditions. Channelization and flow depletion significantly reduced species richness, Shannon-Wiener diversity, and biomass in both macroinvertebrates and fish. Furthermore, we found a significant interaction between river type and flow depletion, as revealed by two-way ANOVA, with macroinvertebrate and fish communities in natural rivers being more sensitive to flow reductions than artificial channels. Redundancy analyses (RDAs) revealed that total phosphorus (TP) was the primary driver of macroinvertebrate community variation (contributing 23.6%), while DO played a crucial role in fish assemblages (contributing 20.6%). These findings underscore the significant impacts of channelization and flow depletion on urban river ecosystems, highlighting the vulnerability of natural rivers to flow depletion. Our study calls for urgent implementation of integrated management strategies to mitigate hydrological alterations, restore natural flow regimes, and reduce nutrient inputs, thereby enhancing the ecological resilience of urban aquatic ecosystems.